Parental Expectations and Developmental Benefits of Early-Age Baby Swimming Activities - Ali, Ghaisania Amanda; Syaodih, Ernawulan; Ali, Rizki Hazazi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Baby swimming for children aged 6-36 months is experiencing increasing popularity. This program involves exercises in the water for 30-60 minutes, water-based activities can serve as another way to foster early childhood skills. Baby swimming's effects include instilling a sense of freedom, strength, and confidence in the water early on, offering diverse sensory experiences, and promoting children's physical and mental development. This study explores parental expectations and perceptions regarding baby swimming and its benefits for infant development. The methodology used is a literature review with a scoping review, following the PRISMA-ScR guidelines and the PICO framework, which consists of Population, Intervention, Comparison, and Outcome. The research results show that parents believe water activities such as baby swimming are good for infants' physical health and children's mental development. Parents' views on baby swimming are influenced by personal experiences, swimming abilities, knowledge, and current trends. Health and developmental advantages for children, alongside economic and environmental considerations, lead parents to select baby swimming. The quality of service dictates their satisfaction.